2007
DOI: 10.1152/ajpheart.01214.2006
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxidative stress in alterations of mitochondrial function in ischemic-reperfused hearts

Abstract: Makazan Z, Saini HK, Dhalla NS. Role of oxidative stress in alterations of mitochondrial function in ischemic-reperfused hearts. Am J Physiol Heart Circ Physiol 292: H1986 -H1994, 2007. First published December 15, 2006; doi:10.1152/ajpheart.01214.2006.-To study the mechanisms of mitochondrial dysfunction due to ischemiareperfusion (I/R) injury, rat hearts were subjected to 20 or 30 min of global ischemia followed by 30 min of reperfusion. After recording both left ventricular developed pressure (LVDP) and end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 51 publications
4
55
0
Order By: Relevance
“…The role of oxidative stress in alterations of mitochondria in ischemia-reperfusion injury and in catecholamine-induced changes in cardiac sarcolemmal Ca 2? transport has already been indicated [33,34]. The present study demonstrated that epinephrine administration is associated with oxidative stress as the plasma levels of MDA, a marker of lipid peroxidation, rose significantly upon injecting cumulative doses of epinephrine.…”
Section: Discussionsupporting
confidence: 68%
“…The role of oxidative stress in alterations of mitochondria in ischemia-reperfusion injury and in catecholamine-induced changes in cardiac sarcolemmal Ca 2? transport has already been indicated [33,34]. The present study demonstrated that epinephrine administration is associated with oxidative stress as the plasma levels of MDA, a marker of lipid peroxidation, rose significantly upon injecting cumulative doses of epinephrine.…”
Section: Discussionsupporting
confidence: 68%
“…In addition to the respiratory burst of inflammatory cells such local ischemia can further induce ROS production via xanthine oxidase conversion from xanthine dehydrogenase. (Chanock et al, 1994;Nishino, 1994;Gute et al, 1998;Makazan et al, 2007).Multiple groups have shown that stem cells appear to have an increased antioxidant capacity (Dernbach et al, 2004;He et al, 2004), whereas others have demonstrated the deleterious role of inflammation and oxidative stress in cell transplantation (Qu et al, 1998;Suzuki et al, 2000). Our group has shown that MDSCs have lower rates of stressinduced cell death, and we have speculated that the MDSCs' increased regenerative capacity may relate to an increased resistance to oxidative and inflammatory stress Deasy et al, 2007).…”
mentioning
confidence: 78%
“…In addition to the respiratory burst of inflammatory cells such local ischemia can further induce ROS production via xanthine oxidase conversion from xanthine dehydrogenase. (Chanock et al, 1994;Nishino, 1994;Gute et al, 1998;Makazan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the precise mechanisms underlying the protective effects of CIHH on ischemic hearts are far from clear. It is well known that oxidative stress and oxygen-derived free radicals [primarily reactive oxygen species (ROS)] contribute to I/R injury [10,11] . Many proteins that have key roles in the homeostasis of cardiomyocytes, such as the Na + /Ca 2+ exchanger and the sodium pump, are modified during massive ROS release [12,13] .…”
Section: Introductionmentioning
confidence: 99%